Cost of herpes zoster and herpes zoster-related complications among immunocompromised individuals. Issue 45 (29th October 2018) - Meyers, Juliana L.; Candrilli, Sean D.; Rausch, Debora A.; Yan, Songkai; Patterson, Brandon J.; Levin, Myron J.
Highlights: Immunocompromised individuals with herpes zoster complications incurred extra costs. Costs occurred primarily in the first quarter after diagnosis. Costs were higher for older patients by each decile except for those 80 years and over. Abstract: Herpes zoster (HZ) is a painful dermatomal rash caused by reactivation of latent varicella-zoster virus. The incidence of HZ is increased for immunocompromised (IC) individuals. The objective of this study is to assess the healthcare costs incurred by IC individuals who develop HZ with or without associated complications. We conducted a retrospective case-control study across the US over a 5-year period, based on health insurance claims data for individuals aged ≥50 years identified as IC by disease or immunosuppressive treatment. A cohort of 30, 107 IC individuals who experienced HZ was matched to a cohort of 113, 875 IC individuals without HZ. Average all-cause healthcare costs over 18 months were calculated and compared between IC individuals with and without HZ. In addition, the costs of HZ in IC individuals with HZ-related complications were compared to the costs of those with uncomplicated HZ. During the year following HZ onset, IC individuals with HZ had on average total unadjusted costs that were US$3879 higher than the controls. After adjusting costs, controlling for comorbidities and healthcare costs before the onset of HZ, the average annual costs for HZ cases and controls without HZ were similar. HZ-related complications led to increases in average adjusted annual costs compared to uncomplicated HZ ranging from US$612 for eye complications to US$4535 for neurologic complications. In conclusion, in IC individuals, episodes of HZ lead to substantially increased unadjusted annual healthcare costs. HZ-related complications add considerably to adjusted annual healthcare costs compared to uncomplicated HZ.